Autoimmune polyendocrine syndrome in a standard poodle with concurrent non‐endocrine immune‐mediated diseases. Issue 3 (26th May 2021) - Kuijlaars, Margaux; Yool, Donald A.; Ridyard, Alison E.
Abstract: A 6‐year‐old female neutered standard poodle was referred with a 4‐week history of rapidly progressive weight loss, muscle atrophy, hyporexia, hind limb weakness and lethargy. In the preceding 3‐month period, the dog had been diagnosed with both keratoconjunctivitis sicca (KCS) and hypoadrenocorticism. Clinical deterioration had occurred despite treatment for hypoadrenocorticism. Following referral, the dog was diagnosed with concurrent hypothyroidism, exocrine pancreatic insufficiency (EPI) and suspected generalised myositis. Treatment with hormone replacement therapy, pancreatic enzyme supplementation and immunosuppressive doses of prednisolone and mycophenolate resulted in marked clinical improvement. This case describes a rapidly progressive, presumed autoimmune, polyglandular endocrinopathy in a dog with concurrent non‐endocrine autoimmune diseases.